The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bjsports-2019-101808
|View full text |Cite
|
Sign up to set email alerts
|

Complete resolution of a hamstring intramuscular tendon injury on MRI is not necessary for a clinically successful return to play

Abstract: BackgroundClinical decision-making around intramuscular tendon injuries of the hamstrings is a controversial topic in sports medicine. For this injury, MRI at return to play (RTP) might improve RTP decision-making; however, no studies have investigated this.ObjectiveOur objectives were to describe MRI characteristics at RTP, to evaluate healing and to examine the association of MRI characteristics at RTP with reinjury for clinically recovered hamstring intramuscular tendon injuries.MethodsWe included 41 athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…Namely, is a complete and thus terminated muscle healing necessary for a successful RTP? According to a previous study of Vermeulen et al [35], this does not seem to be the case. First, it should be mentioned that the study of Vermeulen et al agrees with the previously stated fact that at the moment of RTP (the moment that the athlete seems clinically recovered), MRI does not depict a complete resolution of the hamstring injury [32,35].…”
Section: Methodological Considerationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Namely, is a complete and thus terminated muscle healing necessary for a successful RTP? According to a previous study of Vermeulen et al [35], this does not seem to be the case. First, it should be mentioned that the study of Vermeulen et al agrees with the previously stated fact that at the moment of RTP (the moment that the athlete seems clinically recovered), MRI does not depict a complete resolution of the hamstring injury [32,35].…”
Section: Methodological Considerationsmentioning
confidence: 81%
“…According to a previous study of Vermeulen et al [35], this does not seem to be the case. First, it should be mentioned that the study of Vermeulen et al agrees with the previously stated fact that at the moment of RTP (the moment that the athlete seems clinically recovered), MRI does not depict a complete resolution of the hamstring injury [32,35]. However, the authors reported that the group of athletes that obtained a reinjury showed the same tissue discontinuities on MRI as the group of athletes that had a successful, (re)injury-free RTP [35].…”
Section: Methodological Considerationsmentioning
confidence: 81%
“…Athletes can, however, successfully RTS despite persistent signs of intramuscular tendon disruption on follow-up MRI, without increasing their risk of re-injury. 34 Based on current evidence, practitioners with scope to refer for an MRI may be able to provide a more accurate prognosis for RTS by differentiating between HSIs with and without visible tissue damage or proximal tendon involvement. However, the need to alter rehabilitation and RTS decision-making based purely on other MRI findings, such as intramuscular tendon disruption, requires further investigation before being recommended as standard practice.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Deficits in hamstring muscle structure and function are commonly observed at the time of RTS or even later following HSI, 42,60 but there is little evidence to suggest these variables are associated with re-injury. When measured at RTS, risk of re-injury is increased with greater between-leg deficits in active knee extension ROM and isometric hamstring strength, 47 but unaltered by residual deficits on MRI 34 or isokinetic strength testing. 60 These findings are limited to relatively small sample sizes, highlighting the need to conduct multi-site studies, employing a standard suite of RTS assessments, over several years, to identify variables associated with re-injury risk.…”
Section: Are There Key Rehabilitation Interventions or Is A Multifactorial Approach Essential?mentioning
confidence: 99%
“…And when an injury in the myoconnective junction has a tendon gap (by MRI), the injury will have worst prognosis, require longer time to RTP and could present greater risk of re-injury compared to others injuries. However, a study of full-thickness intramuscular tendon damage, did not show re-injury after 12 months ( Vermeulen et al, 2019 ). Regarding MTJ and MFJ injuries, it is not clear which one has better prognosis and, consequently, less time to RTP ( Balius et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%